L' orientamento unitario della teologia trinitaria di Agostino tra monoteismo gerarchico pagano e "diteismo" ariano. - Territo, Luigi ca. 21. Jh. (Rassegna di teologia, 2025)
This article intends to highlight the unitary orientation of Augustinian Trinitarian reflection. The bishop of Hippo developed a theological reflection on Trinitarian monotheism by engaging with the different reasonings of his interlocutors and interacting with the challenges and opportunities that their philosophical-theological models represented for the development of a Christian intelligere of the Trinitarian mystery, whether they were, Pagans, Neoplatonists, Aryans or Pneumatomachs. In fact, we find in the response to pagan monotheistic syncretism, and to the Arian ditheism of the 4th century, the locus of formation of the unitary orientation the Hipponate's Trinitarian thought.